2021
DOI: 10.1021/acs.jpcc.1c04977
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Ferromagnetism in Exfoliated Ultrathin Pyrite Sheets

Abstract: There has been no experimental evidence for ferromagnetic ordering in isotropic atomically thin two-dimensional crystals, until a bilayer Cr 2 Ge 2 Te 6 and a three-atom thick monolayer CrI 3 is shown to retain ferromagnetic ordering at finite temperatures. Here, we demonstrate successful isolation of a nonvan der Waals-type ultrathin nanosheet of FeS 2 derived from naturally occurring pyrite mineral (FeS 2 ) by means of liquid-phase exfoliation. Structural characterizations imply that (111)-oriented sheets ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Our calculated spin spiral energies using generalized Bloch theorem and also supported by the results from Monte Carlo simulations indicate that the magnetic ground states of the ground state structural phase are not perfectly collinear. During the revision of this paper, the experimental paper are published in JPCC [29]. The authors revised the results as they point out that they observed the ferromagnetic phase, but it only appears at low temperature, which is consistent with our theoretical studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our calculated spin spiral energies using generalized Bloch theorem and also supported by the results from Monte Carlo simulations indicate that the magnetic ground states of the ground state structural phase are not perfectly collinear. During the revision of this paper, the experimental paper are published in JPCC [29]. The authors revised the results as they point out that they observed the ferromagnetic phase, but it only appears at low temperature, which is consistent with our theoretical studies.…”
Section: Discussionsupporting
confidence: 76%
“…In the past, dynamical stability, electronic and magnetic properties of 2D FeS 2 with different surface orientations have been investigated theoretically [23][24][25][26][27]. Very recently, Anand et al have reported the isolation of 2D FeS 2 , and more importantly, they found that it is possible to observe long-range ferromagnetic (FM) order even up to room temperature [28,29]. Their DFT simulations show that the FeS 2 (111) surface is the one that has the lowest formation energy and at the same time has FM configuration as the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…[ 68 ] This work is then followed by the exfoliation of many other minerals such as chromite, [ 70 ] ilmenite, [ 69 ] goethite, [ 75 ] galena, [ 75 ] calcite, [ 75 ] and pyrite. [ 81,82 ]…”
Section: Lpe Of Nonlayered Non‐van‐der‐waals (Nl‐nvdw) Compoundsmentioning
confidence: 99%
“…[30][31][32] 2D FeS 2 has been demonstrated to show ferromagnetic (FM) order at room temperature. 33,34 The symmetry-breaking 2D FeTe 2 is predicted to show excellent stability and room temperature ferromagnetism. 35,36 Besides, high-quality ultrathin 2D FeSe 2 nanosheets have been synthesized by a facile solution method, which further promotes the development of iron chalcogenides.…”
Section: Introductionmentioning
confidence: 99%